2016
DOI: 10.1080/13811118.2016.1162243
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Mindfulness, Depressive Symptoms, and Non-Suicidal Self-Injury Amongst Adolescents

Abstract: Mindfulness is often part of treatment for non-suicidal self-injury (NSSI); however, there has been limited research examining the role of mindfulness in NSSI. Thus, the current study sought to investigate the relationship among mindfulness, depressive symptoms, and NSSI (past year) in adolescents (N = 764; 56.8% female, M age = 14.42, SD = 0.64) with consideration of gender. Adolescents with recent NSSI (n = 74; 83.8% female, M age = 14.36, SD = 0.56) and a matched for age and gender no-NSSI group completed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 70 publications
2
25
1
5
Order By: Relevance
“…Finally, mindfulness did not significantly moderate any paths of either the anxiety or depressive symptom model. Mindfulness refers to an awareness of, but a distancing from, but not resisting or avoiding, one's distressful thoughts and feelings , and has demonstrated clinical utility in addressing anxiety and depression ; as such, our findings seem contradictory to emerging literature suggesting that mindfulness is therapeutically beneficial across an array of mental health outcomes (Chiesa & Serretti, 2011), including NSSI and suicidal behavior (Heath, Carsley, De Riggi, Mills, & Mettler, 2016;Luoma & Villatte, 2012). One reason for the non-significance of our mindfulness-based findings may be due to the differences between mindfulness and the other sub-components of self-compassion.…”
Section: Discussioncontrasting
confidence: 68%
“…Finally, mindfulness did not significantly moderate any paths of either the anxiety or depressive symptom model. Mindfulness refers to an awareness of, but a distancing from, but not resisting or avoiding, one's distressful thoughts and feelings , and has demonstrated clinical utility in addressing anxiety and depression ; as such, our findings seem contradictory to emerging literature suggesting that mindfulness is therapeutically beneficial across an array of mental health outcomes (Chiesa & Serretti, 2011), including NSSI and suicidal behavior (Heath, Carsley, De Riggi, Mills, & Mettler, 2016;Luoma & Villatte, 2012). One reason for the non-significance of our mindfulness-based findings may be due to the differences between mindfulness and the other sub-components of self-compassion.…”
Section: Discussioncontrasting
confidence: 68%
“…One consistent finding within the literature on NSSI among adolescents has been the association between depressive symptoms and NSSI (Heath et al, 2016;Marshall et al, 2013;You and Leung, 2012), particularly among adolescents in clinical settings (Burke et al, 2015;Tuisku et al, 2012). Burke et al (2015) followed 110 adolescents from the US who are at risk for onset of bipolar disorder for 6-months and found that NSSI co-occur with higher levels of depressive symptoms and interpersonal stressful life events at baseline and follow-up.…”
Section: Introductionmentioning
confidence: 76%
“…Individuals with a history of NSSI but none in the past year also report greater acceptance of emotions than those currently engaging in NSSI (Anderson & Crowther, 2012). Further, mindfulness has been shown to partially mediate the relationship between depression and NSSI, highlighting its protective role (Heath, Carsley, De Riggi, Mills, & Mettler, 2016). When NSSI serves the avoidant function of relieving affect perceived as intolerable, fostering mindful awareness of emotion may reduce reliance on this behavior.…”
mentioning
confidence: 99%